Research on the Scheduling Problem of Movie Scenes - Yulian Liu; Qiuji Sun; Xiaotian Zhang; Yiwei Wu (Discrete Dynamics in Nature and Society)
The scheduling problem of movie scenes refers to the reasonable ordering of the shooting sequence of the scene, thereby minimizing the total cost of the movie scenes. This paper considers the factors affecting the cost of movie scenes shooting in the real world and constructs an integer linear programming model. A tabu search based method (TSBM) and a particle swarm optimization based method (PSOBM) are designed to solve larger-scale problems. Numerical experiments show that both TSBM and PSOBM are suitable for solving small-scale movie scenes scheduling problem. Moreover, through the comparison experiments between TSBM and PSOBM, it is verified that the TSBM can effectively solve the large-scale movie scenes scheduling problem.